Analysis of The Capacity of Indonesian School Organizations and Communities Learning Center (CLC) in Sabah, Malaysia - Akadira, Tora; Sunarya, Amud; Sukirman, Sri Ningsih (Universitas Teuku Umar, 2025)
This study analyzes the capacity of Indonesian School Organizations and Community Learning Centers (CLC) in Sabah, Malaysia, to provide education for Indonesian migrant children. The research aims to examine institutional challenges, management differences, and stakeholder involvement in supporting education access. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis. The findings reveal that while both Indonesian Schools (SIKK) and CLCs play crucial roles in migrant education, they face significant challenges, including limited resources, regulatory constraints, and lack of coordination between institutions. SIKK benefits from direct government support, whereas CLCs rely heavily on community and private sector involvement. The study highlights the need for stronger institutional capacity, improved teacher training, and enhanced collaboration between Indonesia and Malaysia. Strengthening policy frameworks and increasing cross-border educational cooperation are essential to ensuring sustainable and inclusive education for Indonesian migrant children. This research provides valuable insights for policymakers, educators, and stakeholders seeking to improve educational access and quality in migrant communities.